Father's involvement in the lives of children in foster care. Issue 1 (12th December 2014) - Icard, Larry D.; Fagan, Jay; Lee, Yookyong; Rutledge, Scott E.
Abstract: Limited understandings exist about non‐resident fathers' views of their involvement with their children in foster care placements. Guided by the ecological systems framework, the purpose of this exploratory study was to gain insights into fathers' perceptions of their involvement with a child in foster care. Data were collected from demographic questionnaires and two focus groups with 17 men. Fathers expressed how kinship compared with non‐kinship placements affected their involvement. Fathers were also in agreement that their financial hardships were a significant factor affecting their involvement. Several fathers also reported how they experienced discrimination in the child welfare system as men. Surprisingly, uncommon to findings from other studies, few men viewed the child's mother as being a barrier to their involvement. The findings provide insights into factors requiring attention to help non‐residential fathers become involved with their children.